Perilaku Administrasi Dalam Pelayanan Publik (Studi Tentang Prismatis Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Malaka) - Quirina Wulandari Rame; Lenny M Tamunu; Laurensius P Say Rani (Jurnal EBI, 2022)
Prismatic behavior is the behavior of people who have both traditional and modern characteristics, in other words, people who are undergoing a transition are people who are moving towards a modern society. The purpose of this study is to explain the behavior of administration in public services to the community at the Department of Population and Civil Registration of Malacca Regency. This study uses Riggs' theory on Prismatic Behavior, especially in the aspects of Formalism and Overlapping. This research is qualitative research with post positivism paradigm. The research location is in the Dispenduk of Malacca Regency, with data collection techniques using observation, interviews and documentation studies. Data analysis used the Miles and Huberman model, namely data collection, data reduction, data presentation and verification. The results is still prismatic behavior in public services in the Malacca District Dispenduk, with the findings in the research, namely: the behavior of the apparatus that is not in accordance with the applicable Standard Operating Procedures, the lack of public awareness of the importance of having population documents, human resources inadequate, and there is still discrimination in services. It is recommended that the Malacca Regency Dispenduk Government comply more with the applicable SOPs, it is necessary to disseminate information to the community, increase human resources and other public service support facilities in order to realize excellent public services at the Malacca Dispenduk. Keywords: Behavior, Prismatic, Formalism, Overlap